Healthcare of Indigenous Amazonian Peoples in response to COVID-19: Marginality, discrimination and revaluation of ancestral knowledge in Ucayali, Peru - Montag D. (2021)
Systematic and persistent discrimination against Indigenous Peoples translates into differential health outcomes when analysed through ethnicity and/or mother tongue.1 In Peru, morbidity and mortality rates among Indigenous Peoples for COVID-19 appear to confirm this